Structured Planning for Strengthening Marketing and Distribution Capacity of Cilembu Sweet Potato Products - Winna Roswinna; Ida Marina; Dety Sukmawati; Deden Komar Priatna; Maria Lusiana Yulianti; Euis Dasipah; Anne Lasminingrat; Adi Oksifa Rahma Harti; Agi Dahtiar (Unram Journal of Community Service, 2024)
The method of implementing this community service is systematically designed to overcome the problems faced by the target partner, Ma Utik, in developing the Cilembu yam industry and its processed products. The preparation and planning stages as well as socialization and initial training are the main focuses in this program. The preparation stage begins with an initial survey to identify partner needs related to marketing, business management, distribution network development, and product innovation. A service team consisting of experts in economics, management, agribusiness, and informatics was formed with a division of tasks according to competence. A structured work plan includes a schedule of activities, implementation methods, and indicators of success, as well as careful management of budgets and resources. Socialization and training materials were developed based on partner needs to ensure in-depth understanding and mastery of relevant skills. The socialization phase begins with an initial meeting to introduce the program's objectives, benefits and solutions to partners, while accommodating their inputs. Initial training was conducted to provide partners with a foundation of knowledge and skills. Marketing strategy training covers the use of social media, digital marketing, branding, and promotion. Business management training covers business planning, financial management, and strategic decision-making using business management software. Distribution network development training includes negotiating and building relationships with distributors, as well as utilizing communication technology. Product innovation training includes identification of market trends and development of new products using market research technology. Through this approach, it is expected that partners can understand the program objectives and acquire the necessary skills to improve their competitiveness. With effective coordination between the service team, community partners, and supporting institutions, this program can run smoothly and have a significant impact. The implementation of a digital marketing application specifically for Cilembu yam products is one of the main results that is expected to increase product visibility, facilitate customer access, strengthen branding, and increase interaction with customers and business partners